Effectiveness of monoclonal antibody therapy for COVID-19 patients using a risk scoring system. Issue 2 (February 2022) - Mutoh, Yoshikazu; Umemura, Takumi; Ota, Aiko; Okuda, Keisuke; Moriya, Ryoma; Tago, Mayumi; Soejima, Kazuaki; Noguchi, Yoichiro; Bando, Tomohiro; Ota, Sho; Sato, Tomonori; Hirota, Shuko; et al.
Abstract: Introduction: Monoclonal antibody therapy has been reported to be highly effective for preventing hospitalisation and severe cases in patients with Coronavirus Disease 2019 (COVID-19). However, since the drug is not readily available, it is important to rapidly and appropriately identify high-risk patients who can benefit most from therapy. Therefore, we designed a risk scoring system to identify at-risk COVID-19 patients in our region during the largest surge of COVID-19, from July to September 2021. Methods: According to the risk scores, confirmed COVID-19 patients were introduced to receive REGN-CoV-2 to our hospital by regional health centre from 18th August (Term 3). The primary outcome was the comparison of the number of hospitalisation and severe condition with other periods, the 4th wave (Term 1) and the early part of the 5th wave (Term 2) in Japan. Results: During Term 3, 115 patients were stratified with the scoring system and administered REGN-COV-2. The number of hospitalisation vs severe cases were 60 (5.2%) vs 14 (1.2%), 8 (1.5%) vs 3 (0.6%) and 21 (1.2%) vs 2 (0.1%), in term 1, 2 and 3, respectively. Among those aged <60 years, compared with term 1, the relative risk of hospitalisation and severe condition were 0.25 (95% CI: 0.12–0.53) and 0.10 (95% CI: 0.01–0.80), respectively, in term 3. Drug adverse events were fever (3: 2.6%), headache (1: 0.9%) and neck rash (1: 0.9%), all events were resolved within 24 h wth no serious adverse event. Conclusions: The administration of monoclonal antibody therapy using a risk scoring system significantly reduced the number of hospitalisation and disease severity of COVID-19 without any serious adverse events and avoided regional medical collapse.